Pelatihan Pemeriksaan Instalasi Tenaga Listrik pada Tenaga Inspektur sesuai Kepmen DJK ESDM di PT. Rekayasa Daya Energi - Salama Manjang; Ikhlas Kitta; Sri Mawar Said; Yusri Yusri; Faizal Arya Samman; Yustinus Sombolayuk; Indar C Gunadin; Gassing Gassing (Faculty of Engineering UNHAS, 2021)
This community service activity aims to build a cooperative relationship between Electrical Engineering Department of Hasanuddin University and company partners in South Sulawesi. One of the company partners engaged in the engineering inspection agency, namely PT. Rekayasa Daya Energi, where some of partner problems are not having experts who have certificates of competence and experience as well as professional expertise in their respective fields, both as permanent and non-permanent experts as field inspectors to meet the requirements required by the Ministry of Energy and Mineral Resources, as the person in charge of Engineering and as a certified Electricity Engineering Personnel inspection in the field of electrical installations. For this reason, knowledge from inspectors is needed to master this field practically which requires a refresher on work competence in the field of electrical power installation inspection. This activity provides training, including inspection techniques for power plant installations, inspection techniques for substation installations and electric power transmission, inspection techniques for electric power distribution installations, and inspection techniques for electrical power utilization installations. The preparation process for the implementation of the training begins by coordinating with potential young workers who are coordinated by partners who are represented through a business entity, namely PT. Energy Engineering is related to the schedule, participants and materials to be given during the training. The implementation team then made several training modules in the form of softcopy as the main training material. Electricity installation inspection training was held for 1 (one) day on 3 September 2020, which was attended by 15 inspectors.